The Effect of Working Capital on the Level of Profitability at PT Indofood Sukses Makmur Tbk in 2016-2019 - Neny Wahyuning Tiyas (Perkumpulan Praktisi Akuntansi Indonesia, 2021)
The purpose of this study was to determine the effect of working capital on the level of profitability at PT Indofood Sukses Makmur Tbk. The use of variables in this study which is Working Capital which is a variable (X) and Profitability is a variable (Y). Research Writing The data used are quantitative data using secondary data and simple linear data analysis which is used for hypothesis testing. This analysis also uses a way to assess the profitability of a company, one of which uses the (Gross Profit Margin) which functions to measure the rate of return of gross profit to the amount of net sales. One of the important things that is needed by the company, including PT Indofood Sukses Makmur Tbk, to operate the company and achieve the company's goals, namely achieving profit or profit, is Working Capital.